TAXPAYER ON MSMES IN RANTAU UTARA DISTRICT, LABUHAN BATU REGENCY - Nisha, Nadya Sapudan; Harahap, Hayanuddin Safri; Na, Novrihan Leily (LPPM Univ. Ibn Khaldun Bogor, 2022)
This service aims to observe and disseminate good perceptions of the effectiveness of the taxation system, knowledge and understanding of tax regulations, and the level of trust in the legal system and government in paying tax compliance. The population in this study is the MSME taxpayer category of private individuals who have a free business in Rantau Utara, Labuhan Batu. This community Service (PKM) activity was carried out by outreach to the community in Rantau Utara, precisely on Jl. H. Adam Malik Gg. Taruna 45. The results of this Community Service Activ (PKM) show that previously MSME members did not know and did not realize what a taxpayer was. So I, as a resource person, conducted a socialization of Taxpayer's Community Service (PKM) to MSMEs in Rantau Utara, telling me what a taxpayer is and the types of taxes.